A coordinated bus bridging and metro short turning model in response to urban metro disruptions. Issue 1 (27th April 2022) - Wu, Zijian; Zhao, Xiaolong; Xiao, Longwen; Wang, Pu
Abstract: When an urban metro disruption occurs, the urban metro usually operates in a short turning mode and bus bridging is the typical way to relink the disconnected stations. For emergency response models dealing with urban metro disruptions, minimizing passenger delay in the bus bridging process and the metro short turning process is usually the optimization objective. In this study, we simultaneously consider the passenger delay in the bus bridging process and the metro short turning process to develop a coordinated emergency response model dealing with urban metro disruptions. The proposed coordinated model is validated in an actual urban metro line using actual passenger boarding demand data. Useful insights in response to urban metro disruptions are obtained.